Biocompatible cellulose-based superabsorbent hydrogels with antimicrobial activity. (10th February 2016) - Peng, Na; Wang, Yanfeng; Ye, Qifa; Liang, Lei; An, Yuxing; Li, Qiwei; Chang, Chunyu
Highlights: The biocompatible hydrogels were fabricated by cross-linking of cellulose and quaternized cellulose in NaOH/urea aqueous solution. The swelling ratio of hydrogel was as high as 984 g/g, showing superabsorbent property. The cellulose based hydrogels exhibited good antimicrobial efficacy against Saccharomyces cerevisiae . Abstract: Current superabsorbent hydrogels commercially applied in the disposable diapers have disadvantages such as weak mechanical strength, poor biocompatibility, and lack of antimicrobial activity, which may induce skin allergy of body. To overcome these hassles, we have developed novel cellulose based hydrogels via simple chemical cross-linking of quaternized cellulose (QC) and native cellulose in NaOH/urea aqueous solution. The prepared hydrogel showed superabsorbent property, high mechanical strength, good biocompatibility, and excellent antimicrobial efficacy against Saccharomyces cerevisiae . The presence of QC in the hydrogel networks not only improved their swelling ratio via electrostatic repulsion of quaternary ammonium groups, but also endowed their antimicrobial activity by attraction of sections of anionic microbial membrane into internal pores of poly cationic hydrogel leading to the disruption of microbial membrane. Moreover, the swelling properties, mechanical strength, and antibacterial activity of hydrogels strongly depended on the contents of quaternary ammonium groups in hydrogel networks. The obtained data encouraged the use of these hydrogels for hygienic application such as disposable diapers.